Novel High-Resolution Imaging Using ANTERION Optical Coherence Tomography to Assess Fluid Reservoir Change in Scleral Lens Periphery. Issue 11 (8th November 2022) - Tran, Stephanie; Roberts, Cynthia J.; Mahmoud, Ashraf; Pisano, Stephanie; Mundy, Chantelle
Abstract : Objectives: To assess scleral lens fluid reservoir (FR) change simultaneously in four quadrants with single acquisition using novel ANTERION anterior segment swept-source optical coherence tomography (SS-OCT). Methods: A prospective, observational, clinical study of 18 subjects (30 eyes) was performed on adults fitted with a scleral lens for ocular surface disease (n=8), irregular cornea/scar (n=7), and corneal ectasia (n=15). ANTERION anterior segment SS-OCT imaging was obtained at the initial visit and at the follow-up to determine pre and post scleral lens settling, measured in microns, centrally and peripherally. Peripheral measurements were grouped into four quadrants. Repeated-measures ANOVA was performed comparing vault post minus pre differences by quadrant, and TTests comparing difference in FR by lens design were performed with a significant threshold at P <0.05. Results: The mean central scleral lens settling was significant at −48.3±41.7 μm. The change in FR by quadrant was superior (S): −47.8±67.3 μm, inferior (I): −68.0±102.2 μm, nasal (N) −46.3±63.4 μm, and temporal (T): −56.7±49.3 μm. There were no significant differences in lens settling between the quadrants. Within the three categories, the irregular cornea group experienced significantly greater lens settling. There was no significant difference in central FR when comparing lens design or lens diameter. Conclusions: The ANTERION SS-OCT allows for high-resolution central and peripheral assessment of FR in scleral lens wear. With increased technology available for scleral lens customization, this imaging modality can assist in more detailed assessment in quadrant-specific scleral lens designs.